Advancements in Energy Storage Technologies - Chen, Xiangping; Cao, Wenping (IntechOpen, 2018)
Energy storage technologies play an important role in terms of high-efficient energy utilisation and stable energy flow in the system. This book provides a glimpse of some latest advancements in energy storage technologies, management and control, innovative energy conversion, energy efficiency and system integration. It is aimed at providing a guideline for developing similar storage systems and for the readers who are interested in energy storage-related technologies, wind energy, solar energy, smart grid and smart buildings.